The Gamma-ray Transients Monitor (GTM) on board Formosat-8B and its GRB detection efficiency. Issue 2 (15th January 2022) - Chang, Hsiang-Kuang; Lin, Chi-Hsun; Tsao, Che-Chih; Chu, Che-Yen; Yang, Shun-Chia; Huang, Chien-You; Wang, Chao-Hsi; Su, Tze-Hsiang; Chung, Yun-Hsin; Chang, Yung-Wei; Gong, Zi-Jun; Hsiang, Jr-Yue; et al.
Abstract: The Gamma-ray Transients Monitor (GTM) is a secondary payload on board Formosat-8B (FS-8B), a Taiwanese remote-sensing satellite scheduled to launch in 2024. The goal of GTM is to monitor Gamma Ray Bursts (GRBs) and other bright gamma-ray transients in the energy range from 50 keV to 2 MeV. GTM consists of two identical modules located on two opposite sides of FS-8B. Each module has four sensor units facing different directions to cover half of the sky. The two modules will then cover the whole sky, including the direction occulted by the Earth. Each sensor unit is composed of a GAGG scintillator array (50 mm × 50 mm × 8 mm) to be readout by SiPM with 16 pixel-channels. We describe the instrument design and its GRB detection efficiency in this paper. GTM is expected to detect about 40 GRBs per year.